Tabletop wargames a designers' and writers' handbook - Priestley, Rick (Pen & Sword Military, 2016)
"Unlike chess or backgammon, tabletop wargames have no single, accepted set of rules. Most wargamers at some point have had a go at writing their own rules and virtually all have modified commercially available sets to better suit their idea of the ideal game or to adapt favorite rules to a different historical period or setting. But many who try soon find that writing a coherent set of rules is harder than they thought, while tweaking one part of an existing set can often have unforeseen consequences for the game as a whole. Now, at last, help is at hand. Veteran gamer and rules writer John Lambshead has teamed up with the legendary Rick Priestley, creator of Games Workshop's phenomenally successful Warhammer system, to create this essential guide for any would-be wargame designer or tinkerer. Rick and John give excellent advice on deciding what you want from a wargame and balancing 'realism' (be it in a historical or a fantasy/sci-fi context) with playability. They discuss the relative merits of various mechanisms (cards, dice, tables) then discuss how to select and combine these to handle the various essential game elements of turn sequences, combat resolution, morale etc to create a rewarding and playable game that suits your tastes and requirements.